European modernity a global approach - Stråth, Bo 1943-; Wagner, Peter 1956- (Europe's legacy in the modern world, 2017)
It is often taken for granted that modernity emerged in Europe and diffused from there across the world. This book questions that assumption and re-examines the question of European modernity in the light of world history. Bo Strath and Peter Wagner re-position Europe in the global context of the 19th and 20th0centuries. They show that Europe is less modern than has been assumed, and modernity less European and thus decentre Europe in a way that makes room for a wider historical perspective. Adopting a thematic structure, the authors reconceive the idea of European modernity in relation to key topics such democracy, industrial revolution and religion